STATE MECHANISMS FOR SOLVING THE MENTAL PROBLEMS OF CHILDREN AND ADOLESCENTS - Norakidze, Tinatin; Arutinova, Luiza (Georgian Psychological Journal, 2023)
In order to improve the mental health of children and adolescents, prevent the existing and potential problems and deal with them effectively, it is of primarily importance to study the overall situation in this area, work on future approaches based on the findings and their implementation. The present research discusses the existing situation related to the mental health of children and adolescents over the last twenty years on the examples of various countries, including Georgia. The aim is to study the problems, the changes that have happened and fresh initiatives to deal with the problems, as well as appropriate assistance mechanisms and the recommendations suggested to the countries by professionals.